Implikasi Perceraian Perkawinan Campuran Terhadap Hak Waris Anak dalam Peraturan Perundang-Undangan Indonesia - Makmur, Indira Nur Syahrani; Andita, Naufalia; Rajagukguk, Elisabeth Immanuella; Pasaribu, Erika Esteria; Tarina, Dwi Desi Yayi (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
Mixed marriages between Indonesian citizens (WNI) and foreign nationals (WNA) often complicate joint asset division and children's inheritance rights, especially in divorces without prenuptial agreements. This article explores these implications through the case of Erna Yonita (WNI) and Eric Van Druten (WNA), who married in 2011 and divorced in 2022 without a prenuptial agreement. Despite legal challenges, they resolved asset division amicably and ensured equal inheritance rights for their children. The article also examines Indonesian regulations and challenges in mixed marriage inheritance cases.